PREDICTION OF DENGUE CASES IN KUPANG, EAST NUSA TENGGARA PROVINCE, INDONESIA - Respati, Titik; Wanti, Wanti; Nindrea, Ricvan Dana (International Journal of Public Health Science (IJPHS), 2020)
With the pandemic of Corona Virus [Covid-19], another infectious disease such as Dengue neglected in Indonesia. Since the majority of resources, both human and capital, are focusing more on Covid-19, it is still essential to also manage Dengue as it is still becoming a threat to the community. This study aims to predict the number of cases of Dengue in Kupang, East Nusa Tenggara, Indonesia. This study area is in Kupang City, East Nusa Tenggara Province, Indonesia. The Data regarding monthly Dengue reported cases by months from January 2010 ? December 2019 in Kupang City collected to describe the temporal patterns of dengue cases. The Box-Jenkins approach used to fit the Auto-Regressive Integrated Moving Average [ARIMA] models. This model will predict monthly dengue cases for the year 2020 [12 months]. Data analyzed using the Minitab program version 18.0. This study shows that seasonality was an essential component for Kupang City, which performed an exploratory analysis of dengue incidence [ln data] for 2010-2019. The linear trend model shows the prediction of dengue cases in 2020 was Yt = 36.9 ? 0.131 x t. The forecast tells that Dengue will remain high for the whole year. Maintaining a clean environment, reduction of breeding sites, and other protective measurements against dengue transmission is significant to perform.Keyword:Covid-19Dengue CasesCases Prediction